A Inclusão do deficiente visual e a flexibilização curricular: o estado de conhecimento nos Programas de Pós-Graduação - BORGES, Roseli Nazaré Torres Magno (2022)
This study seeks to map research on the school inclusion of students with visual impairments and the process of curricular flexibility in the postgraduate Programs in Education. The survey took place catalog of theses and dissertations, analyzing abstracts from 2014 to 2019. The research called state of knowledge aims to collect data on the knowledge produced regarding the subject, through the mapping of other researchers on what has already been published. The results indicated a significant production in the research on the inclusion of blind students and little emphasis on the curricular issue. Regarding the theoretical methodological axis, the works adopt a qualitative approach, the theoretical foundations were mainly: post-structuralist perspective, historical cultural approach and phenomenology, the types of research described were case study, cartography, and ethnographic study and autobiography. In the results, the researches point to advances and setbacks in the inclusion of visually impaired students, with an emphasis on exclusionary practices that make learning difficult. From this balance, it is possible to outline new challenges in research involving mainly the issue of curricular flexibility.